Analysis of corner kicks at the FIFA Women`s World Cup 2019 in relation to match status and team quality - Lee, J.; Mills, S. (International Journal of Performance Analysis in Sport, 2021)
This study analysed the characteristics of 476 corner kicks taken during 52 matches at the FIFA women`s World Cup 2019. The effect of current match status/team quality was examined, and the corner characteristics associated with the 17 goals scored from corners (3.6%) and 93 shots on-target (19.5%) were identified. Goals from corners were more likely from dynamic attacks or with 1-4 defenders for short corners. Shots on-target were more likely from corners delivered into GA3&CA3 and the outer zones, =6 attackers were inside the delivery area or involved =3 intervening attackers. Match status was significantly associated with number of defenders, attackers for short corners, defenders for short corners and type of marking. Team quality was significantly associated with type of delivery, kicking foot, number of attackers, attackers for short corners, defenders for short corners, defenders on posts, number of intervening attackers and offensive organisation. Team quality was not significantly associated with corner outcomes, perhaps a consequence of higher-quality teams not always favouring corner characteristics which are associated with increased success (goals or shots on-target). These results can assist coaches to understand corner characteristics to expect when winning, drawing, or losing, or against different levels of opposition within women`s international football.